WEAK VERBS USED IN THE WORK AND THEIR STATISTICAL, MORPHOLOGICAL AND SEMANTIC ANALYSIS - Marhabo Meliboyeva (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
this article examines the comparison of incorrect verbs on the works of arab, Russian and Uzbek nahvers.